The legacy of industrial Khabarovsk in the early 20th century - Smolianinova, Tatiana (project baikal, 2025)
The article is devoted to industrial objects of the historical part of the city of Khabarovsk of the early 20th century. The work presents the interim results of a scientific study conducted within the framework of the project entitled “Methods of integration of historical development zones and preservation of cultural heritage sites in the context of development of a large city”. The locations of preserved historical industrial objects are analyzed. Three key objects are considered, these are the complex of buildings of Tifontai, the Khlebnikov distillery and the refrigerator building. It was proposed to include them in the museum and exhibition framework of the city.